Pengembangan Aplikasi Web Pelacakan Harga Situs Web E-commerce - Muhammad Fandy Fahreza Ramadhana Fauzi; Satrio Agung Wicaksono; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In 2017, five e-commerce sites in Indonesia with the highest number of unique visitors experienced an average growth of 97 percent. With this significant growth, new e-commerce companies must use various methods in order to compete in this industry. However, there are e-commerce that use unfavorable methods, for example using the "fake discount" tactics, where the discount given looks fantastic, but the discount is given after the original price of the item is raised first. Users are not aware of this because they do not remember the price before the change, and there is no display of the product price history. Based on these problems, the Web Application for Price Tracking of E-Commerce Website can be developed which can be used by e-commerce users to track prices, by entering product links into the application, then the application get the product prices with scraping techniques and then the results are saved in a database as the price history for that product. This application development uses the waterfall model development method, and the results of the implementation are tested by validation testing, performance testing, and User Acceptance Testing (UAT). The validation test obtained a value of 100% valid, performance testing shows the application has good performance, and majority of the respondents on UAT testing give a positive score without any negative, so it can be concluded that the Web Application for Price Tracking of E-Commerce Website can be a solution to e-commerce's prices and discounts problem.